Synthesis, characterization and antibacterial activity of superparamagnetic nanoparticles modified with glycol chitosan - Baskaran Stephen Inbaraj, Tsung-Yu Tsai and Bing-Huei Chen (Science and Technology of Advanced Materials, 2012)
Iron oxide nanoparticles (IONPs) were synthesized by coprecipitation of iron salts in alkali media followed by coating with glycol chitosan (GC-coated IONPs). Both bare and GC-coated IONPs were subsequently characterized and evaluated for their antibacterial activity. Comparison of Fourier transform infrared spectra and thermogravimetric data of bare and GC-coated IONPs confirmed the presence of GC coating on IONPs. Magnetization curves showed that both bare and GC-coated IONPs are superparamagnetic and have saturation magnetizations of 70.3 and 59.8 emu g−1, respectively. The IONP size was measured as ~8–9 nm by transmission electron microscopy, and their crystal structure was assigned to magnetite from x-ray diffraction patterns. Both bare and GC-coated IONPs inhibited the growths of Escherichia coli ATCC 8739 and Salmonella enteritidis SE 01 bacteria better than the antibiotics linezolid and cefaclor, as evaluated by the agar dilution assay. GC-coated IONPs showed higher potency against E. coli O157:H7 and Staphylococcus aureus ATCC 10832 than bare IONPs. Given their biocompatibility and antibacterial properties, GC-coated IONPs are a potential nanomaterial for in vivo applications.